2014
DOI: 10.4161/19336950.2014.959408
|View full text |Cite
|
Sign up to set email alerts
|

When S1P meets ATP

Abstract: Burow P, Klapperst€ uck M, Markwardt F. Activation of ATP secretion via volume-regulated anion channels by sphingosine-1-phosphate in RAW macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Sphingosine kinase 1 (SPHK1), the most important synthetase for sphingosine-1-phosphate (S1P), is involved in tumour progression in various cancer cells [[18], [19], [20], [21]]. Studies have shown that VRAC can be activated by S1P and that high expression of SPHK1/S1P promotes the proliferation of HCC [21,22]. Because SWELL1 is an essential component of VRAC, we speculated about the possible relationship between SPHK1 and SWELL1 in the proliferation of HCC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sphingosine kinase 1 (SPHK1), the most important synthetase for sphingosine-1-phosphate (S1P), is involved in tumour progression in various cancer cells [[18], [19], [20], [21]]. Studies have shown that VRAC can be activated by S1P and that high expression of SPHK1/S1P promotes the proliferation of HCC [21,22]. Because SWELL1 is an essential component of VRAC, we speculated about the possible relationship between SPHK1 and SWELL1 in the proliferation of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…For further confirmation, MMP and intracellular ATP measurements were analysed, and the results were in agreement with ROS measurements. Moreover, S1P has been found to induce ATP secretion by activating the VRAC [22], and ATP is a known growth factor for tumour cells [39,40]. Thus, to some degree, the enhancement effect of SWELL1 on ATP content also verified the proliferative effect of the SPHK1-SWELL1-PKCa pathway on HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1P induced ATP release via VRAC formed an autocrine link between inflammatory sphingolipid and purinergic signaling in macrophages (Burow P et al, 2015) and microglia (Zahiri D et al, 2021). S1P is an inflammatory mediator and is produced by sphingosine kinase, which is activated by several inflammatory signaling molecules, including bacterial b b lipopolysaccharide (LPS), PDGF, TNFα, thrombin, IgE-bound antigen and ATP (Burow P et al, 2015; Burow P and Markwardt F, 2014). S1P is rich in the cancer microenvironment (Nagahashi M et al 2012) and plays important roles in cancer progression via diverse pathways of its G-protein coupled receptors, which implicates S1P pathway as a therapeutic target (Pyne NJ and Pyne S, 2010; Ogretmen B, 2018; Nagahashi M et al, 2018).…”
Section: Discussionmentioning
confidence: 99%